(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The organizational and legal provision of security of confidential cooperation in Ukraine has been analyzed. The information on modern problems of ensuring security of the Institution of confidential cooperation has been systematized. The risks arising during the confidential cooperation have been outlined. The author has raised the issue of keeping the balance in ensuring security of a confidant’s personality on the one hand and the need of procedural recording of the information obtained from the confidant on the other hand. Normative and legal regulation of protecting confidants in Ukraine and abroad has been compared. The problematic issues of guarantees for the protection of confidants in the Ukrainian legislation have been revealed; the ways to solve them have been offered. The protective mechanisms that in one form or another should be applied to the confidants have been analyzed: guarantees of social and legal protection, restrictions on the use of certain categories of persons as confidants, etc. The issue of ensuring the safety of the confidants after the cooperation with law enforcement agencies has been raised. The author has offered to establish appropriate security measures for such confidants, to determine the reasons and grounds for the application of such measures, and to outline the mechanism of the implementation of such measures at the regulatory level. The limits of permissible behavior of confidants during the fulfillment of crime counteraction tasks have been studied. It has been offered to supplement the Art. 43 of the Criminal Code of Ukraine with the norm that would extend the rights of persons who under the law, perform a special task by participating in an organized group or criminal organization, to confidants, who assist law enforcement agencies in preventing and/or investigating a serious or particularly serious crime. In the context of involving a confidant in accomplishing the tasks of criminal investigation, the author has offered to provide a separate, secret investigative (search) action, which, by analogy with the norm of the Art. 272 of the Criminal Procedural Code of Ukraine should be conducted according to the resolution of an investigator, agreed with the head of the pre-trial investigation agency, and the decision of a prosecutor.